Isolation, cloning and expression of CCA1 gene in transgenic progeny plants of Japonica rice exhibiting altered morphological traits. - Ashok Chaudhury; Anita Devi Dalal; Nayan Tara Sheoran (PLoS ONE, 2019)
Circadian clock genes holds tremendous potential for breeding crops better adapted to environmental fluctuations inherent to climate change. Endogenous TOC1 promoter and CCA1 gene from rice were isolated, cloned and mobilized into pCAMBIA1300 vectors and RNAi constructs A, B and C. Embryogenic calli of varying ages derived from mature seeds of Taipei 309 were employed for Agrobacterium-mediated genetic transformation generating T0, T1 and T2 independent transgenic lines were analyzed for over-expression and repression of CCA1 gene along with various morphological traits. Six hundred and thirty two T0 transgenic plants were generated from rice calli using constructs A, B and C. T0 progeny plants derived from constructs A, B and C did not show any considerable difference in morphological traits. T1and T2 progeny plants derived from construct A exhibited over-expression of CCA1 gene, on the contrary, progeny plants derived from RNAi constructs B and C exhibited repression of CCA1 gene in qRT-PCR analysis at different time points and showed rhythmicity peaking at dawn (6:00 AM) and lowest expression at 12:00 Noon. T1 and T2 progeny plants derived from construct A, namely, A-17 and A-45 exhibited reduced number of tillers/panicles (6-8), reduced thousand seed weight (10.1-16.6g), decreased seed length (4.98 to 6.58mm), decreased seed width (1.1-1.8mm) as compared to wild type plants. T1 and T2 progeny plants of construct B and C showed increased number of tillers/panicles (8-19), better seed yield (4.98-28.9g), increased thousand seed weight (15.6-29.03g), slightly increased seed length (5.7-7.43mm) and slightly increased seed width (1.7-2.98mm) as compared to wild type plants. Chlorophyll content in T1 and T2 progeny plants did not show any significant difference among the three constructs, however, rhythmicity was observed over the period of time in conjunction to CCA1 gene expression. Evidence has been presented which demonstrates that endogenous repression of CCA1 gene resulted in improved morphological traits: increased number of tillers/panicle, thousand seed weight, seed size; whereas, over-expression leads to diminution in morphological traits: decreased number of tillers/panicle, thousand seed weight, seed size as compared to the wild type in T1 and T2 progeny plants. This is first report of successful regulation of endogenous CCA1 gene under control of TOC1 promoter and its effect on improved growth vigor in Japonica rice.